ANALISIS PENGARUH PDRB, BELANJA MODAL, JUMLAH PENDUDUK, DAN INFLASI TERHADAP PENDAPATAN ASLI DAERAH: Studi Kasus Pada Pemerintah Daerah Kabupaten/Kota Di Wilayah Provinsi Jawa Barat - RAMDANI, DIAN; Darmansyah; Nurmala Ahmar (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Regional Original Revenue is the revenue obtained by the region from sources withinits own region which is collected based on regional regulations in accordance withapplicable laws and regulations. The purpose of this study was to examine andanalyze the effect of Gross Regional Domestic Product (GRDP), CapitalExpenditure, Population, and Inflation on Regional Original Income. In addition,the purpose of this study is also to analyze whether the variables of Population andInflation can moderate the effect of other independent variables on RegionalOriginal Revenue. The data used in this study is secondary data sourced from theCentral Statistics Agency of West Java Province, Regional Government FinancialReports (LKPD) of the Regency / City Government in West Java Province, andpublication data on the portal or website of the Ministry of Finance Finance of theRepublic of Indonesia, as well as other valid sources of information and literature.Based on the results of the study, it shows that the Total Population and Inflation partially affect the Regional Original Revenue and the Total Population andInflation moderate the influence of GRDP on the Regional Original Revenue.Besides, the results of this study also explain that Capital Expenditure and GrossRegional Domestic Product partially have no effect on Regional Original Revenue